Imaging Findings and MRI Patterns in a Cohort of 18q Chromosomal Abnormalities - Malik, Prateek; Branson, Helen; Yoon, Grace; Shroff, Manohar; Blaser, Susan; Krishnan, Pradeep (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The abnormalities of the long arm of chromosome 18 (18q) constitute a complex spectrum. We aimed to systematically analyze their MR imaging features. We hypothesized that there would be variable but recognizable white matter and structural patterns in this cohort.MATERIALS AND METHODS: In this retrospective cohort study, we included pediatric patients with a proved abnormality of 18q between 2000–2022. An age- and sex-matched control cohort was also constructed.RESULTS: Thirty-six cases, median MR imaging age 19.6 months (4.3–59.3), satisfied our inclusion criteria. Most were female (25, 69%, F:M ratio 2.2:1). Fifty MR imaging studies were analyzed, and 35 (70%) had delayed myelination. Two independent readers scored brain myelination with excellent interrater reliability. Three recognizable evolving MR imaging patterns with distinct age distributions and improving myelination scores were identified: Pelizaeus-Merzbacher disease–like (9.9 months, 37), intermediate (22 months, 48), and washed-out pattern (113.6 months, 53). Etiologically, MRIs were analyzed across 3 subgroups: 18q deletion (34, 69%), trisomy 18 (10, 21%), and ring chromosome 18 (5, 10%). Ring chromosome 18 had the highest myelination lag (27, P = .005) and multifocal white matter changes (P = .001). Trisomy 18 had smaller pons and cerebellar dimensions (anteposterior diameter pons, P = .002; corpus callosum vermis, P < .001; and transverse cerebellar diameter, P = .04).CONCLUSIONS: In this cohort of 18q chromosomal abnormalities, MR imaging revealed recognizable patterns correlating with improving brain myelination. Imaging findings appear to be on a continuum with more severe white matter abnormalities in ring chromosome 18 and greater prevalence of structural abnormalities of the pons and cerebellum in trisomy 18.18q-18q deletion18qlong arm of chromosome 18APDanteroposterior diameterCCcorpus callosumCCDcraniocaudal diameterFODfronto-occipital diameterGWMDgray-white matter differentiationPMDPelizaeus-Merzbacher diseaseTCDtransverse cerebellar diameter